SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KONSENTRASI BIDANG ILMU EKONOMI MENGGUNAKAN METODE WEIGHTED AVERAGE DAN FUZZY FIS TSUKOMOTO ( Studi Kasus Program Magister Manajemen IIB Darmajaya ) - Suci Mutiara; Yulmaini -; RZ Abdul Aziz (IIB Darmajaya, 2019)
Postgraduate IIB Darmajaya in Management program in its curriculum offers concentration subjects in the third semester. Concentrations in the field of economics are grouped into three concentrations namely marketing, human resources (HR) and finance (Finance). In the third-semester students are required to choose one concentration of the field of economics according to their competence. But the obstacle is often found in the choice of concentration in the field of economics is that many students still unable recognize their interests and abilities. Besides, many students who choose the concentration in the field of economics only follow the most specialization, but do not follow based on their abilities. According to that, it requires the tool to able to provide decision support in term of selecting concentrations based on predetermined considerations. The methods used in solving this problem are Weighted Average Method and Tsukomoto Fuzzy FIS Method with 4 (four) input variables and 3 (three) output variables. Input variables consist of subject values, interest values, motivation values , and abilities. While the output variable consists of marketing concentration, human resources (HR) and finance (Finance) The sample was taken from second semester students of Master of Management.The test results show that the recommendation for the selection of the right concentration for these students is Financial specialization with a Defuzzification value of 65.91 higher than Marketing and Human Resources specialization which is 64,69 and 64,59, respectively Keywords: Decision Support System, Weighted Average Method, Tsukomoto Fuzzy FIS Method, Concentration